Estudiantes con un vocabulario pobre: un problema que se origina desde la infancia / Students with poor vocabulary: a problem that originates from childhood - Álvarez Xochihua, Omar; Arce Ruelas, Karla Ivette; Paez Manjarrez, Patricia; González Fraga, José Ángel (Revista Internacional de Aprendizaje en la Educación Superior, 2017)
ABSTRACT A proficient oral and written communication is considered as one of the main competencies that determines a favorable performance of students at different educational levels. Being the level of vocabulary of students a relevant factor that determines their ability to understand and learn new knowledge. However, differences in the vocabulary level among students from different educational levels have not been specified. This article reports the results of using the Vocabulary Assessment System based on Images, from an exploratory study conducted with 283 elementary, middle, high school and university freshman students. RESUMEN Una proficiente comunicación oral y escrita es considerada como una competencia que determina el desempeño favorable de los estudiantes en sus distintos niveles educativos. Siendo el dominio de vocabulario un factor que determina la capacidad de comprender y aprender nuevo conocimiento. Sin embargo, no se ha precisado un comparativo sobre el nivel de vocabulario presente en los distintos niveles educativos. En este artículo se presentan los resultados al utilizar el Sistema para la Evaluación de Vocabulario en Imágenes, obtenidos de un estudio exploratorio donde se evaluó el dominio de vocabulario de 283 estudiantes de educación básica, media superior y superior.